Fractal dimensionality of a coiled helical coil - Kak, Subhash (Journal of bioinformatics and computational biology, 2025)
The helical coil is ubiquitous in biological and natural systems, and it is often the basic form in complex structures. This paper considers the question of its dimensionality, , in biological information as the helical coil goes through recursive coiling as in DNA and RNA molecules in chromatin, in which the -value is a function of the lengthening of the curve. It is shown that the dimensionality of coiled coils is virtually equal to . Of the three forms of DNA, the dimensionality of the B-form is nearest to the optimal value, and this might be the reason why it is most common.